Addition of oxaliplatin to neoadjuvant radiochemotherapy in MRI‐defined T3, T4 or N+ rectal cancer: a randomized clinical trial. Issue 6 (10th May 2017) - Haddad, Peiman; Miraie, Monir; Farhan, Farshid; Fazeli, Mohammad‐Sadegh; Alikhassi, Afsaneh; Maddah‐Safaei, Afsaneh; Aghili, Mahdi; Kalaghchi, Bita; Babaei, Mohammad
Abstract: Background: Clinical trials investigating the effects of addition of oxaliplatin to neoadjuvant radiochemotherapy in locally advanced rectal cancers (LARCs) have brought controversial results for pathologic complete response as an endpoint. This randomized clinical trial investigated downstaging as a short‐term surrogate for progression‐free survival (PFS). Methods: Patients with magnetic resonance imaging (MRI) defined T3, T4 or N+ histologically proven adenocarcinoma of rectum within 15 cm from anal verge were randomly assigned to receive 50–50.4 Gy external beam radiation in 25–28 fractions and concurrent capecitabine 825 mg/m 2 twice daily 5 days a week with or without oxaliplatin 60 mg/m 2 weekly as neoadjuvant radiochemotherapy (Capox and Cap group, respectively). T downstage was defined as at least one stage regression in pathologic report after surgery comparing to MRI image before the preoperative treatment. Adverse effects of treatment were recorded on a weekly basis according to National Cancer Institute Common Toxicity Criteria, version 4. Results: Sixty‐three patients were randomly assigned to Cap ( n = 31) and Capox ( n = 32) groups. There was no grade 4 toxicity. The only grade 3 toxicity that occurred more in Capox group was diarrhea (22% vs 0%; P = 0.006). Histopathologic stage of 52 patients (27 patients in Cap and 25 patients in Capox groups) was compared to their preoperative stage defined by MRI. There was a greater rate of T downstage in Capox group (59% vs 42%; P = 0.037). Eleven patients in Capox group (34%) achieved pathologic complete response, comparing to four in Cap group (13%); P = 0.072. Conclusion: The addition of oxalipatin to neoadjuvant radiochemotherapy in LARC led to higher rate of tumor downstaging. Longer follow‐up is needed to evaluate PFS.